The Evolution From Nielsen Ratings to Social Media Metrics in Indonesian Broadcasting - Widodo, Suko; Aji, Gagas (Institut Seni Indonesia Yogyakarta, 2025)
This study investigates the digital transformation of Indonesian television broadcasters as they migrate from traditional analog broadcasting to digital platforms, with a focus on TikTok, Instagram, and YouTube. Using descriptive quantitative analysis and engagement rate data sourced from Phlanx, the research evaluates the performance of five major national TV stations—SCTV, RCTI, Trans TV, Metro TV, and tvOne—across their official and sub-branded social media accounts. Findings reveal that while some broadcasters, notably SCTV and RCTI, demonstrate strategic adaptation through content segmentation, thematic branding, and audience engagement, others rely on outdated broadcasting logic that limits interactivity and digital resonance. The presence of verification (blue tick) is shown to enhance perceived credibility but does not guarantee engagement without platform-specific content strategies. The study concludes that successful digital migration depends not merely on presence but on the ability to adopt platform-native storytelling, build interactive communities, and reorganize media workflows to align with audience expectations in a participatory, algorithm-driven ecosystem.